Order dependent spatial properties of high harmonic generation - Lloyd, D; O'Keeffe, K; Hooker, S (Optical Society of America, 2014)
We report on the dependence of the spatial properties of high harmonic generation on the harmonic order. We present interesting features in the transverse spatial coherence which may be important for coherent imaging experiments.Research in Optical Sciences © OSA 2014.